(untitled) (Shahid Kirti Multidisciplinary Journal, 2026)
Knowledge is a fundamental resource for both business enterprises and higher education institutions (HEIs). This study aims to identify the personal factors and social media influencing knowledge sharing among faculties of community college in Kathmandu. This study followed descriptive and causal comparative research design. Based on the social interaction theory, it found that that personal factors (knowledge self-efficacy, social trust and social interaction) and social media have significant impact on knowledge sharing among faculties in Kathmandu. The findings have both practical and theoretical implications. They can provide guidelines for educators and key personal who are leading community colleges. The results equally helpful in developing strategies and policies to promote knowledge sharing culture in community colleges.